BIMBINGAN ROHANI DAN PENGARUHNYA TERHADAP PENURUNAN TINGKAT KECEMASAN PADA IBU PRIMIGRAVIDA DENGAN PERSALINAN KALA I DI RSU BANYUMAS - Darwanti,; Handoyo,; Kamaluddin, Ridlwan (Jurusan Keperawatan FIKES UNSOED, 2007)
Deliveries is monumental time to women, this critical situation is causing anxiety, which makes stiff to pelvis muscle, pursuing miometrium activity and increasing deliveries pattern malfunctions. Spiritual guidance is one of many methods which guide by dzikir and praying which would gave mentality strength and restrains incredible physical distress, because of giving strong confidential. This research objective was to prove spiritual guidance influence to decrease anxiety level of primigravida mothers with phase I baby deliveries at Banyumas Public Hospital. This research was Quasi Experimental method with non equivalent control group pre test and post test design. Respondent of this research was giving birth mothers at delivering room of Banyumas Public Hospital and fulfill inclusion criteria. The number of respondent was 68 mothers which consist of 34 respondents as experiment group, 34 respondents as control group. Sampling methods was purposive sampling. Anxiety level measuring was manifest anxiety scale from Taylor (T-MAS). Data were analyzed by using unavailable and wilcoxon rank sum test, with p < 0,05 or ÃŽÂ± 5%. Wilcoxon rank sum test was showing count value at 17,5. Seen from p value P: 0,00, which means smaller than ÃŽÂ± : 5 %. Therefore null hypotesis was rejected and alternative hypothesis was accepted. This means that Ã¢â‚¬Å“Spiritual guidance give significant influence to decrease of Anxiety level of primigravida mothers with phase 1of baby deliveriesÃ¢â‚¬Â. Conclusion of the research is that Ã¢â‚¬Å“Spiritual guidance gives significant influence to decrease anxiety level of primigravida mothers with phase I baby deliveriesÃ¢â‚¬Â